Needs Analysis of Strengthening Civic Disposition through Future Learning Design to Enhance Students’ Citizenship Character - Ni Kadek Rahayu Sukadani; Dewa Bagus Sanjaya; I Nengah Suastika (Universitas Sebelas Maret, 2026)
The rapid development of technology and globalization has created significant challenges for students’ citizenship character, including declining responsibility, tolerance, and social awareness. In elementary Citizenship Education (PKn), learning practices often emphasize cognitive achievement over the strengthening of civic dispositions, leading to limited internalization of civic values in authentic social contexts. Previous studies have rarely examined the integration of Future Learning Design (FLD) in strengthening civic disposition at the elementary level. Therefore, this study aimed to analyze the need for strengthening civic disposition through FLD to enhance students’ citizenship character in elementary schools. This study employed a descriptive survey design with qualitative support. The participants were 46 elementary school teachers in Sawan District, Bali, selected through purposive sampling. Data were collected using questionnaires consisting of Likert-scale and open-ended items and analyzed using descriptive statistics and qualitative analysis techniques. The findings revealed that civic values such as responsibility, tolerance, and respect for diversity had been relatively well integrated into classroom practices. However, reflective learning, critical thinking activities, and technology integration remained limited. Teachers also expressed a strong need for innovative learning strategies and FLD-based instructional tools to support future-oriented civic learning. The study concludes that Future Learning Design is a relevant framework for strengthening civic disposition through contextual, student-centered, reflective, and technology-supported learning experiences in elementary Citizenship Education.